A morbillivirus causing mass mortality in seals. - Osterhaus, A.D.M.E. (Albert) (Vaccine, 1989)
During an outbreak of a serious apparently infectious disease among harbour seals (Phoca vitulina), which started in the Kattegat area in April 1988 and rapidly spread to the North sea, the Wadden sea and the Baltic sea, greater than 17,000 animals died within a period of eight months. In August 1988 it was realized that the clinical symptoms and pathological lesions were similar to those found in canine distemper: apart from general depression and fever, the animals suffered from severe respiratory, gastrointestinal and central nervous disease and a variety of viral, bacterial and parasitic infections were frequently encountered, suggesting a severe malfunctioning of the immune system. At different expert meetings, held in several of the countries involved, possible explanations for the deaths were not only attributed to an infectious agent, but also to effects of overpopulation and environmental pollution. Seroepizootiological studies and the failure of vaccination experiments suggested that a herpesvirus and a picornavirus, which had been isolated from dead seals at the beginning of the outbreak, were opportunistic infections occurring in animals suffering from another infection rather than being the primary cause of the outbreaks. Serological studies were then extended to other viruses of carnivores, known to cause similar symptoms. Screening of a large panel of seal sera from the Netherlands, Denmark, FRG, Sweden and the UK, collected before and during the outbreak, in a virus neutralization test for the presence of canine distemper virus (CDV) neutralizing antibodies, indicated that CDV or a closely related morbillivirus was the primary cause of the disease outbreak.(ABSTRACT TRUNCATED AT 250 WORDS)